2013
DOI: 10.3390/rs5062688
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Mapping Using Simulated Worldview-3 Short-Wave-Infrared Imagery

Abstract: WorldView commercial imaging satellites comprise a constellation developed by DigitalGlobe Inc. (Longmont, CO, USA). Worldview-3 (WV-3), currently planned for launch in 2014, will have 8 spectral bands in the Visible and Near-Infrared (VNIR), and an additional 8 bands in the Short-Wave-Infrared (SWIR); the approximately 1.0-2.5 μm spectral range. WV-3 will be the first commercial system with both high spatial resolution and multispectral SWIR capability. Airborne Visible/Infrared Imaging Spectrometer (AVIRIS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 19 publications
1
63
0
1
Order By: Relevance
“…The recently launched Worldview-3 sensor has 8 SWIR bands, of which four were taken from the ASTER design [25]. Sentinel-2 lacks such narrow bands in the SWIR bands (Figure 1), and van der Meer et al [4] then also concluded that proxies obtained with Sentinel-2 were the same as what could be obtained with Landsat, albeit on a slightly higher spatial resolution.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…The recently launched Worldview-3 sensor has 8 SWIR bands, of which four were taken from the ASTER design [25]. Sentinel-2 lacks such narrow bands in the SWIR bands (Figure 1), and van der Meer et al [4] then also concluded that proxies obtained with Sentinel-2 were the same as what could be obtained with Landsat, albeit on a slightly higher spatial resolution.…”
Section: Introductionmentioning
confidence: 52%
“…First, the field-of-view of the Sentinel-2 bands can be expected to differ from what we obtained with a spatial degradation by pixel aggregation. The actual point spread function of the Sentinel-2 sensor will sample a slightly larger field-of-view than what we used by the exact given pixel size in following [25]. Secondly, the lossy compression of data used on-board Sentinel-2 was not taken into account.…”
Section: Application To Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…After the spectral resampling, the data were spatially resampled from the original 4 m pixel resolution to the 20 m resolution of Sentinel-2A MSI bands. This was done following Kruse and Perry [48] using pixel aggregation (neighbourhood averaging). The subset of the study area was eventually covered by 402 × 201 pixels of 20 × 20 m.…”
Section: Methodsmentioning
confidence: 99%
“…Multispectral and superspectral imagery have been effectively used for mapping geology/minerals [7][8][9][10][11] as well as for monitoring mining impacts [12][13][14][15][16][17][18][19]. However, with a low number of rather broad spectral bands, these systems provide only discrete spectral information (e.g., the state-of-the-art Sentinel-2 sensor has 13 spectral bands [20].…”
Section: Introductionmentioning
confidence: 99%